Faktor-Faktor yang Mempengaruhi Tax Avoidance - Anis Susilowati; Riana Rahmawati Dewi; Anita Wijayanti (Universitas Batanghari Jambi, 2020)
The research aims to determine the influence of company size, leverage, profitability, sales growth, audit committee, and cash flow operations against tax avoidance. Dependent variables in this study are tax avoidance while the independent variables used in this research are company size, leverage, profitability and audit committees. This research is focused on the LQ45 company listed on the Indonesia Stock Exchange (IDX) period 2015-2018. The selection of samples in this study used the purposive sampling method, thus obtained a sample of 51 sample data from the LQ45 company population listed on the Indonesia Stock Exchange (IDX) period 2015-2018. The analytical tools used in this study are multiple linear regression analyses. The results of this research show that the variable cash flow operations affect the tax avoidance, while the company size variables, leverage, profitability, sales growth and audit committees do not affect the tax avoidance.